Dampak strategi quick write berbantuan media animasi terhadap keterampilan menulis teks persuasi siswa - Alnovgada, Valents Roni Sunarno (Universitas Mulawarman, 2024)
This research is motivated by the need for innovation in the learning process in the Industrial Revolution 4.0 era. This research aims to determine the impact of the quick write (QW) strategy assisted by animation media on the ability to write persuasive texts for class VIII students. This research implemented a pretest-posttest control group design involving students from SMP Negeri 5 Pontianak. Students were divided into two groups consisting of 64 students selected through cluster random sampling. The instrument consists of essay questions in the form of a pre-test and post-test. The data were analyzed using the t-test and the results showed that 1) students who were treated with the QW strategy assisted by animation media showed a significant increase in their ability to write persuasive texts, and 2) the QW strategy assisted by animation media contributed to student independence in learning to write, students were active and able to highlight the argument process quickly and responsively related to actual problems with the linguistic skills they have. These findings show that students who use the QW strategy assisted by animation media have a better improvement in their ability to write persuasive texts than students who use direct learning.